Inventory Best Practices. - Bragg, Steven M. (Hoboken : John Wiley & Sons, 2011)
The latest and most important information for best practices in the inventory function. Inventory Best Practices, Second Edition offers the latest and most important information on advanced techniques and strategies to improve on the accuracy of all ongoing inventories, configure a warehouse for optimum counting efficiencies, and more.: Explains the difference between different types of distressed merchandise for disposal purposes; Shows how to maximize the efficiency of inventory tracking systems by shifting selected inventory items into floor stock; Examines inventory picking, storage, trans.
Inventory Best Practices; Contents; Preface; 1 Success or Failure with Best Practices; 2 Inventory Purchasing; 3 Inventory Receiving and Shipping; 4 Inventory Storage; 5 Inventory Picking; 6 Production Issues Impacting Inventory; 7 Inventory Transactions; 8 Inventory Planning and Management; 9 Warehouse Layout; 10 Cost Accounting; 11 Bills of Materials; 12 Impact of Constraints on Inventory; 13 Inventory Policies and Procedures; 14 Inventory Measurements; APPENDIX: Summary of Inventory Best Practices; Glossary; About the Author; Index.
Print version record.
John Wiley and Sons
Keywords: Inventories; Inventory control; Gestion des stocks; inventorying; BUSINESS & ECONOMICS -- Accounting -- Managerial; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; Inventories; Inventory control